Carbon aerogels with atomic dispersion of binary iron–cobalt sites as effective oxygen catalysts for flexible zinc–air batteries. Issue 23 (3rd June 2020) - Chen, Yang; Hu, Shengqiang; Nichols, Forrest; Bridges, Frank; Kan, Shuting; He, Ting; Zhang, Yi; Chen, Shaowei
Abstract : Hydrogel is used as a structural template and precursor to prepare carbon aerogel doped with Fe–Co bimetal sites as bifunctional catalysts for ORR and OER, which exhibits enhanced activity and stability, as compared to the monometal counterparts. Abstract : Iron single atom catalysts have emerged as one of the most active electrocatalysts towards the oxygen reduction reaction (ORR), but the unsatisfactory durability and limited activity for the oxygen evolution reaction (OER) has hampered their commercial applications in rechargeable metal–air batteries. By contrast, cobalt-based catalysts are known to afford excellent ORR stability and OER activity, due to the weak Fenton reaction and low OER Gibbs free energy. Herein, a bimetal hydrogel template is used to prepare carbon aerogels containing Fe–Co bimetal sites (NCAG/Fe–Co) as bifunctional electrocatalysts towards both ORR and OER, with enhanced activity and stability, as compared to the monometal counterparts. High-resolution transmission electron microscopy, elemental mapping and X-ray photoelectron spectroscopy measurements demonstrate homogeneous distributions of the metal centers within defected carbon lattices by coordination to nitrogen dopants. X-ray absorption spectroscopic measurements, in combination with other results, suggest the formation of FeN3 and CoN3 moieties on mutually orthogonal planes with a direct Fe–Co bonding interaction. Electrochemical measurements show that NCAG/Fe–Co delivers a small ORR/OER potential gap of only 0.64 V at the current density of 10 mA cm −2, 60 mV lower than that (0.70 V) with commercial Pt/C and RuO2 catalysts. When applied in a flexible Zn–air battery, the dual-metal NCAG/Fe–Co catalyst also shows a remarkable performance, with a high open-circuit voltage of 1.47 V, a maximum power density of 117 mW cm −2, as well as good rechargeability and flexibility. Results from this study may offer an ingenious protocol in the design and engineering of highly efficient and durable bifunctional electrocatalysts based on dual metal-doped carbons.